SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/103195-ms
|View full text |Cite
|
Sign up to set email alerts
|

World's First Gravel-Packed Uniform Inflow Control Completion

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe Etame oil field, offshore Gabon, West Africa, has been producing since September 2002. The Etame oil reservoir is an oval-shaped, low-relief structure with a moderate aquifer drive. In order to maximize ultimate field recovery, the ET-6H well was drilled with a horizontal lateral positioned to traverse the reservoir near the structural crest and to be within the Upper Gamba sandstone throughout its length. The Gamba sandstone averages 45 ft in thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The spiral channel-type ICDs were verified to keep the fluid flow in the wellbore uniform, so as to avoid large differential pressure, and could extend the lifetime of horizontal wells . In 2006, it was first confirmed that ICDs had the effect of stabilizing the fluid flow in the wellbore and delaying the bottom water breakthrough in the gravel layer . The nozzle-type ICD changed the spiral flow channel of the original ICD, generating a large pressure drop when the fluid passes through the nozzle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spiral channel-type ICDs were verified to keep the fluid flow in the wellbore uniform, so as to avoid large differential pressure, and could extend the lifetime of horizontal wells . In 2006, it was first confirmed that ICDs had the effect of stabilizing the fluid flow in the wellbore and delaying the bottom water breakthrough in the gravel layer . The nozzle-type ICD changed the spiral flow channel of the original ICD, generating a large pressure drop when the fluid passes through the nozzle.…”
Section: Introductionmentioning
confidence: 99%
“… 5 In 2006, it was first confirmed that ICDs had the effect of stabilizing the fluid flow in the wellbore and delaying the bottom water breakthrough in the gravel layer. 6 The nozzle-type ICD 7 changed the spiral flow channel of the original ICD, generating a large pressure drop when the fluid passes through the nozzle. It could work well in increasing the friction resistance at the root of the wellbore where bottom water coning occurred, limiting the water flow into the wellbore and balancing the fluid pressure inside the wellbore.…”
Section: Introductionmentioning
confidence: 99%